VERBAL SUGGESTIVE FORMULAS USED IN MULTIMODAL SUGGESTIVE PSYCHOTHERAPY - Manilov, Igor (PSYCHOLOGICAL JOURNAL, 2020)
The paper considers some theoretical and practical aspects of verbal suggestion used in Multimodal Suggestive Psychotherapy. It shows that general directivity of verbal suggestions in Multimodal Suggestive Psychotherapy is associated with the following psychotherapeutic tasks: correction of dysfunctional cognitive formations; training to gain skills of adaptive thinking and behavior. The paper presents the list of verbal suggestions used in traditional suggestive psychotherapy and emphasizes the distinctive characteristics of verbal suggestions used in Multimodal Suggestive Psychotherapy. It notes that psychotherapeutic suggestions on personal ideal lifestyle are principal and useful. It also explains necessity to use the technique of psychotherapeutic confrontational suggestions and heterogeneous suggestions of the ideas-principles on continuous changeability, interdependence, relativity, irreversibility, self-organization, dynamic equilibrium, uncertainty of meanings, conditionality of frames, continuity and contradictions. The examples of certain verbal suggestive formulas used for treatment of different mental and behavioral disorders are presented. These formulas of suggestion are universal and there is the possibility to use them at heterogeneous and autogenous suggestions. Every formula is described in general and the features of their practical application are also considered. The verbal suggestive formulas were selected based on the performed analysis of data obtained from individual psychotherapeutic sessions with 348 clients. The sample consisted of the clients with neurotic disorders caused by stress or somatic disorders, non-complicated affective disorders, mature personality disorders and some behavioural syndromes (sex dysfunction; disorders of sleep, eating behavior). The implementation of verbal suggestions used in Multimodal Suggestive Psychotherapy assists clients to gain adaptive forms of thinking, make quick correction of their world vision; keep up their positive mood; master specific coping strategies; independently formulate psychotherapeutic goals; maintain a high level of motivation and stimulate constructive activities.